Carbon nanotube and carbon black composite conductive filler and pvc conductive composite material and preparation method thereof
Patent Information
- Application Number
- CN202510231065.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2026-08-28
AI Technical Summary
[0005]本发明针对现有碳纳米管和炭黑原位制备复合导电填料的加热温度高从而导致复合材料的导电和补强性能有不利的技术问题,目的在于提供一种碳纳米管和炭黑复合导电填料
[0028]1) This invention modifies carbon nanotubes and carbon black to graft -COOH and/or -OH onto the sidewalls and endwalls of carbon nanotubes, and graft -COOH and/or -OH onto the surface of carbon black.
Smart Images

Figure CN122647778A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material preparation technology, specifically relating to a carbon nanotube and carbon black composite conductive filler and a PVC conductive composite material and its preparation method. Background Technology
[0002] Carbon nanotubes, as one-dimensional nanomaterials, possess excellent physical and mechanical properties. They are primarily composed of one to dozens of coaxial cylindrical tubes formed by hexagonally arranged carbon atoms. Based on the number of wall layers, they can be classified into single-walled carbon nanotubes and multi-walled carbon nanotubes. Carbon nanotubes exhibit outstanding strength, elasticity, electrical conductivity, and thermal conductivity, thus showing broad application prospects in numerous fields such as new energy, rubber and plastic composite materials, electrochemical materials, and optoelectronic sensing.
[0003] Carbon nanotubes, especially in rubber-plastic composites, serve as conductive fillers, significantly improving the electrical conductivity of these materials. However, simply filling all rubber-plastic materials with carbon nanotubes would be prohibitively expensive, firstly because the manufacturing cost of carbon nanotubes is extremely high; and secondly... Figure 1 As shown, carbon nanotubes have a large aspect ratio, and adjacent carbon nanotubes are prone to entanglement, forming micron-sized or even millimeter-sized aggregates. Therefore, they are difficult to disperse during use, which greatly reduces the effective contact area between carbon nanotubes and PVC resin, preventing the conductivity of carbon nanotubes from being maximized.
[0004] Patent document CN108047495B discloses a method for high-temperature in-situ preparation of a super-strong composite filler of carbon nanotubes and carbon black. This method produces a perfect, grape-like conductive structure with pre-mixed carbon nanotubes as the main component and the generated carbon black particles as beads. The organic combination of dots and lines forms a three-dimensional conductive network, greatly improving conductivity and reinforcement. However, this method requires three stages of heating for in-situ preparation of the composite conductive filler. One stage requires strict temperature control between 1400℃ and 1700℃. Too low a temperature results in a higher proportion of amorphous carbon, while too high a temperature leads to excessively rapid formation and insufficient grape-like structure, both negatively impacting the conductivity and reinforcement properties of the composite material. Furthermore, the in-situ preparation process is quite demanding, posing challenges for industrial scale-up. Summary of the Invention
[0005] This invention addresses the technical problem that the high heating temperature in the existing in-situ preparation of composite conductive fillers using carbon nanotubes and carbon black leads to adverse effects on the conductivity and reinforcing properties of the composite material. The purpose is to provide a composite conductive filler using carbon nanotubes and carbon black.
[0006] The carbon nanotube and carbon black composite conductive filler of this invention comprises a composite material of carbon nanotubes and carbon black obtained by ball milling and mixing surface-grafted carbon nanotubes and surface-grafted carbon black. This invention uses pre-mixed carbon nanotubes as the main component, connecting ordinary carbon black particles to the carbon nanotubes with a coupling agent to form a perfect, beaded, grape-like structure, without requiring high temperatures, thus significantly reducing manufacturing costs. At this point, ordinary carbon black becomes superconducting carbon black, greatly improving the conductivity of the carbon black and reducing the amount of carbon nanotubes used as filler.
[0007] Preferably, the weight ratio of the carbon nanotubes to the carbon black is 1:1 to 4, more preferably 1:2 to 3.
[0008] Preferably, the composite conductive filler further includes a silane coupling agent. Preferably, the weight ratio of the carbon nanotube to the silane coupling agent is 1:0.2 to 0.6, more preferably 1:0.3 to 0.5, and the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0009] Preferably, the composite conductive filler further includes a dispersant. Preferably, the weight ratio of the carbon nanotube to the dispersant is 1:0.4 to 1, more preferably 1:0.6 to 0.8. The dispersant is one or two of ethylene bis-stearamide and pentaerythritol stearate.
[0010] Another objective of this invention is to address the stringent conditions of in-situ preparation processes in the prior art by providing a method for preparing the carbon nanotube and carbon black composite conductive filler described in this invention. The method involves ball milling and grinding surface-grafted carbon nanotubes and surface-grafted carbon black to obtain the carbon nanotube and carbon black composite conductive filler.
[0011] Preferably, the addition of the silane coupling agent before ball milling is preferred, wherein the weight ratio of the carbon nanotubes to the silane coupling agent is 1:0.2 to 0.6, more preferably 1:0.3 to 0.5, and the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane; more preferably, the addition of the dispersant before ball milling is preferred, wherein the weight ratio of the carbon nanotubes to the dispersant is 1:0.4 to 1, more preferably 1:0.6 to 0.8, and the dispersant is preferably one or two of ethylene bis-stearamide and pentaerythritol stearate.
[0012] Preferably, the surface-grafted carbon nanotubes are carbon nanotubes with -COOH and / or -OH grafted onto their surfaces; more preferably, the surface-grafted carbon nanotubes are carbon nanotubes grafted by acid oxidation, preferably using concentrated nitric acid and hydrochloric acid for acid oxidation grafting, more preferably, the mixed acid solution used for acid oxidation grafting includes: 68% concentrated HNO3: 30% hydrochloric acid: deionized water in a volume ratio of 1-3:1:2-3, the acid oxidation grafting temperature is 70℃-90℃, preferably 80℃, the acid oxidation grafting time is 1.5 hours-3 hours, preferably 2 hours, more preferably, the acid oxidation grafted carbon nanotubes are washed with water and dried;
[0013] The carbon nanotubes are single-walled carbon nanotubes, few-walled carbon nanotubes, and / or multi-walled carbon nanotubes.
[0014] The surface-grafted carbon black is carbon black with -COOH and / or -OH grafted onto its surface. Preferably, the surface-grafted carbon black is surface-grafted using vaporized maleic anhydride in a closed contact with carbon black. The grafting temperature is 220℃~260℃, preferably 240℃, and the grafting time is 1.5 hours~3 hours, preferably 2 hours. More preferably, the weight ratio of carbon black to maleic anhydride is 1:0.4~0.6, preferably 1:0.5. More preferably, the surface-grafted carbon black is washed and dried.
[0015] Preferably, the grinding is performed with grinding balls for 3 to 5 hours at a rotation speed of 500 to 1000 rpm, preferably 700 to 800 rpm. Preferably, the diameter of the grinding balls is 2 to 20 mm, preferably 5 to 10 mm. Preferably, the grinding balls are zirconium balls.
[0016] The present invention relates to the application of carbon nanotube and carbon black composite conductive filler in the electrical conductivity, thermal conductivity, and reinforcement of plastic and rubber products.
[0017] This invention provides a PVC conductive composite material, comprising a carbon nanotube and carbon black composite conductive filler, PVC (polyvinyl chloride) resin powder, toughening agent, stabilizer, and antioxidant; preferably, based on 100 parts of PVC resin powder, the following components are included: 3 parts of carbon nanotube, 3-12 parts (preferably 6-9 parts) of carbon black, 0.6-1.8 parts (preferably 0.9-1.5 parts) of silane coupling agent, 1.2-3 parts (preferably 1.8-2.4 parts) of dispersant, 2-10 parts of stabilizer, 5-20 parts of toughening agent, and 0.1-1 parts of antioxidant.
[0018] Preferably, the toughening agent is selected from one or more of the following: dioctyl phthalate, dibutyl phthalate, DOTP (dioctyl terephthalate), epoxidized soybean oil, MBS (methyl methacrylate-butadiene-styrene terpolymer), CPE (chlorinated polyethylene), and ACR (methyl methacrylate grafted crosslinked silicone acrylate rubber).
[0019] The stabilizer is selected from one or more of the following: lead salt composite stabilizers (such as tribasic lead sulfate, dibasic lead phosphite), calcium-zinc composite stabilizers (such as calcium stearate, zinc stearate, and epoxy fatty acid calcium), barium-zinc composite stabilizers and potassium-zinc composite stabilizers (such as potassium zinc ferrous phosphate, dipotassium zinc ferric phosphate, etc.), and organic-based stabilizers (such as IRGANOX 1726, butyltin mercaptan, etc.).
[0020] The antioxidant is selected from one or more of antioxidant 168, antioxidant 1010 and antioxidant 1076.
[0021] Another object of the present invention is to provide a method for preparing the PVC conductive composite material of the present invention, the method comprising the following steps:
[0022] Step S1: PVC resin and additives are mixed to obtain PVC primary mixture; preferably, the additives are toughening agents, stabilizers and antioxidants;
[0023] Step S2: The carbon nanotube and carbon black composite conductive filler is stirred and mixed with PVC mixture to obtain a premix; this allows the carbon nanotube and carbon black composite conductive filler to be mixed more evenly in the PVC premix, and the mixing process causes less damage to the grape-like structure of the carbon nanotube and carbon black composite conductive filler compared to subsequent extrusion.
[0024] Step S3: Pour the premix into an extruder and knead and extrude to obtain PVC conductive composite material.
[0025] Preferably, step S3 involves adding the premix from the main feed port of a twin-screw extruder and then compounding and extruding it through the twin-screw extruder to obtain a PVC conductive composite material.
[0026] The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
[0027] The positive and progressive effects of this invention are as follows:
[0028] 1) This invention modifies carbon nanotubes and carbon black to graft -COOH and / or -OH onto the sidewalls and endwalls of carbon nanotubes, and graft -COOH and / or -OH onto the surface of carbon black.
[0029] 2) The modified carbon nanotube and carbon black composite conductive filler of this invention is achieved by combining carbon nanotubes and carbon black, such as... Figure 2 The conductive filler shown forms a "grape bunch" structure. This structure utilizes the long axial structure of carbon nanotubes to extend the axial length of carbon black and form a rich conductive network, changing the point-like conductivity of carbon black into linear conductivity. Therefore, the coupling of the two can significantly improve the conductivity.
[0030] 3) The PVC conductive composite material of the present invention uses carbon nanotubes and carbon black composite conductive filler. Carbon black is filled in the mesh gaps of carbon nanotube agglomerates. The carbon nanotube agglomerates gradually expand due to the addition of carbon black. Since the carbon nanotube agglomerates are dispersed into multiple strands, and the carbon black filling between the carbon nanotubes acts as grinding beads, it can promote the grinding and dispersion of carbon nanotubes, shorten the grinding time, and the carbon nanotubes are not easy to agglomerate again after being dispersed in PVC resin.
[0031] 4) The carbon black of the present invention, such as Figure 3 The image shows ordinary reinforcing carbon black, which can achieve good conductivity without the need for expensive conductive carbon black, thus greatly reducing costs.
[0032] 5) In the preparation method of the PVC conductive composite material of the present invention, the amount of carbon nanotubes and carbon black added is relatively small, with the amount of carbon nanotubes added being about 2% and the amount of carbon black added being about 5%, which can achieve good conductivity and reinforcement effect while reducing cost. Attached Figure Description
[0033] Figure 1 SEM images of existing carbon nanotubes;
[0034] Figure 2 SEM image of the processed carbon nanotubes;
[0035] Figure 3 SEM image of the treated carbon black;
[0036] Figure 4 The image shows a SEM image of the carbon nanotube and carbon black composite conductive filler prepared in Example 2. Detailed Implementation
[0037] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0038] Examples 1-4
[0039] Preparation of carbon nanotube and carbon black composite conductive filler
[0040] Step SA: Place 5 portions of carbon nanotubes into M A A portion of a mixture of 68% concentrated HNO3, 30% hydrochloric acid, and deionized water in a volume ratio of 1:1:3 was prepared at T. A1 Stirring and acidification at ℃ for 3-5 hours to oxidize and graft carbon nanotubes, grafting -COOH and -OH onto the sidewalls and endwalls of the carbon nanotubes. Then wash with water and filter 6-8 times until the pH of the filtrate is neutral. Then proceed to T... A2 The carbon nanotubes were dried at ℃ to constant weight to obtain the treated carbon nanotubes. The carbon nanotubes used were multi-walled carbon nanotubes GT-210, with a purity ≥90%, diameter = 7~15nm, and length ≤50μm.
[0041] Step SB: Place part M1 of carbon black N220 in a sealed environment and add part M... B maleic anhydride in portions, and heated to T. B1 Maleic anhydride is vaporized at ℃, sealed for 1-3 hours to allow sufficient grafting of -COOH and / or -OH onto the carbon black surface, then washed with water and filtered until the pH of the filtrate is neutral, and then... B2 The carbon black was dried to constant weight at a temperature of ℃ to obtain the treated carbon black.
[0042] Step SC: Add 3 parts of treated carbon nanotubes, 2 parts of treated carbon black (M2), 2 parts of dispersant PETS, and 1 part of silane coupling agent to a grinding mill according to the specified ratio. (The text abruptly ends here, likely due to an incomplete sentence or missing information.) C A composite conductive filler of carbon nanotubes and carbon black was obtained by grinding zirconium balls at a rotation speed of rpm and a diameter of d mm for tc hours.
[0043] Preparation of PVC conductive composite materials
[0044] Step S1: Add 100 parts of PVC resin powder, 5 parts of toughening agent DOTP, 8 parts of toughening agent CPE, 2 parts of toughening agent ACR, 6 parts of stabilizer calcium zinc stabilizer, and 0.5 parts of antioxidant 1010 to a rotary mixer and mix evenly at T1℃ and R1rpm to obtain PVC initial mixture.
[0045] Step S2: Divide the PVC premix into n equal parts. After adding carbon nanotube and carbon black composite conductive filler to the first part, add more carbon nanotube and carbon black composite conductive filler every 10-30 minutes. Mix in powder form at T2℃ and stir at R2 rpm to disperse in solid state, forming a premix. This method allows for pre-dispersion of the PVC premix with the carbon nanotube and carbon black composite conductive filler. Furthermore, stirring, which has less impact on the structure of the carbon nanotube and carbon black composite conductive filler, is chosen instead of direct shear mixing in the extruder, thus minimizing damage to the structure of the carbon nanotube and carbon black composite conductive filler.
[0046] Step S3: The premix is fed into the twin-screw extruder from the main feed port of the twin-screw extruder, mixed, extruded, cooled, and pelletized to obtain PVC conductive composite material;
[0047] The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
[0048] Comparative Example 1
[0049] Preparation of PVC conductive composite materials
[0050] Step S1: Add 100 parts of PVC resin powder, 15 parts of toughening agent, 6 parts of stabilizer, and 0.5 parts of antioxidant to a rotary mixer and mix them evenly at 300 rpm in powder form at 100°C to obtain PVC initial mixture.
[0051] Step S2: Mix 30 parts of carbon black N220 with PVC premix at 100°C in powder form at 200 rpm, disperse in solid form, and form a premix.
[0052] Step S3: The premix is fed into the twin-screw extruder from the main feed port of the twin-screw extruder, mixed, extruded, cooled, and pelletized to obtain PVC conductive composite material;
[0053] The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
[0054] Comparative Example 2
[0055] Preparation of PVC conductive composite materials
[0056] Step S1: Add 100 parts of PVC resin powder, 15 parts of toughening agent, 6 parts of stabilizer, and 0.5 parts of antioxidant to a rotary mixer and mix them evenly at 300 rpm in powder form at 100°C to obtain PVC initial mixture.
[0057] Step S2: Mix 12 parts of superconducting carbon black SP with PVC premix at 100°C in powder form at 200 rpm, disperse in solid form, and form a premix.
[0058] Step S3: The premix is fed into the twin-screw extruder from the main feed port of the twin-screw extruder, mixed, extruded, cooled, and pelletized to obtain PVC conductive composite material;
[0059] The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
[0060] Comparative Example 3
[0061] Preparation of PVC conductive composite materials
[0062] Step S1: Add 100 parts of PVC resin powder, 15 parts of toughening agent, 6 parts of stabilizer, and 0.5 parts of antioxidant to a rotary mixer and mix them evenly at 300 rpm in powder form at 100°C to obtain PVC initial mixture.
[0063] Step S2: Mix 5 parts of GT-210 with PVC premix at 100°C in powder form at 200 rpm to disperse in solid form and form a premix.
[0064] Step S3: The premix is fed into the twin-screw extruder from the main feed port of the twin-screw extruder, mixed, extruded, cooled, and pelletized to obtain PVC conductive composite material;
[0065] The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
[0066] Comparative Example 4
[0067] Preparation of PVC conductive composite materials
[0068] The difference between Comparative Example 4 and Example 2 is that step S2 is deleted, while the other steps remain unchanged.
[0069] Table 1. Raw material component content and product test results of Examples 1-4 and Comparative Examples 1-4
[0070]
[0071]
[0072] Note: The silane coupling agent is γ-aminopropyltriethoxysilane, the toughening agent DOTP is dioctyl terephthalate, and the dispersant PETS is pentaerythritol stearate.
[0073] The test methods are as follows:
[0074] Conductivity test: Conductivity was tested using a weighted resistance meter (PRS-801), and the sample size was a 100×100×3mm square plate.
[0075] Mechanical property testing: Notched impact strength of simply supported beams, using a pendulum impact testing machine.
[0076] Surface smoothness: The surface condition of the extruded sample is observed by the naked eye and divided into three levels: excellent, good, and poor. Excellent means that there are almost no pits on the surface, good means that there are a few pits on the surface, and poor means that there are a lot of pits on the surface.
[0077] like Figure 1 The image shown is a SEM image of the carbon nanotubes before treatment. The surface of the carbon nanotubes is relatively smooth. After treatment, the SEM images of the carbon nanotubes and carbon black obtained using the preparation method of Example 2 are shown below. Figure 2 , Figure 3 As shown, the surface of the carbon nanotubes is rougher, indicating successful grafting. Since carbon black consists of spherical particles, its appearance does not change significantly before and after treatment.
[0078] Figure 4 The image shows an SEM image of the carbon nanotube and carbon black composite conductive filler prepared in Example 2. As can be seen from the image, in the prepared composite conductive filler, the treated carbon black is uniformly coated on the surface of the treated carbon nanotubes. Compared with the carbon nanotubes before the carbon black was compounded, the diameter of the carbon nanotubes in the composite conductive filler is significantly smaller, indicating that after compounding and grinding, the carbon black particles enter the interior of the carbon nanotube bundles, and the treated carbon nanotubes are better dispersed.
[0079] Regarding surface smoothness: As shown in Table 1, the PVC conductive composite material obtained using the preparation method provided by this invention has superior surface smoothness, with almost no pitting on the product surface, indicating that the carbon nanotubes and carbon black conductive materials are uniformly dispersed in the PVC conductive composite material. Compared with Example 2, Comparative Example 4, because the carbon nanotubes and carbon black composite conductive filler were not premixed with the premixed material but directly extruded through an extruder, reduced the uniformity of dispersion of the carbon nanotubes and carbon black composite conductive filler in the PVC material, resulting in a small number of pitting on the product surface.
[0080] Regarding notched impact strength: In Examples 1-4, especially Examples 1-3, the average notched impact strength of the PVC conductive composite materials prepared is significantly higher than that of the PVC conductive composite materials prepared in Comparative Examples 1 and 2. This may be because the conductive agent in Comparative Examples 1 and 2 is carbon black, with an addition amount of 30 parts and 12 parts per 100 parts of PVC, respectively. The large addition of the conductive agent reduces the impact strength of the PVC product itself. Although the conductive agent content in Example 3 is also 12 parts, the PVC conductive composite material preparation method provided by this invention still achieves high impact resistance. In Comparative Example 3, the conductive agent is carbon nanotubes, and the addition amount is relatively small, thus maintaining higher impact resistance. Compared with Example 2, in Comparative Example 4, the carbon nanotube and carbon black composite conductive filler was not premixed with the premixed material but directly extruded through an extruder, which reduced the dispersion uniformity of the carbon nanotube and carbon black composite conductive filler in the PVC material, and thus affected the notched impact strength of the product.
[0081] In the embodiments, the proportion of carbon nanotube and carbon black composite conductive filler in PVC resin is 6-15 parts, preferably 9-12 parts.
[0082] Regarding surface resistivity: For PVC conductive composite materials, a surface resistivity of 10 is generally required. 6 The surface resistivity of the PVC conductive composite material is measured to be Ω / sq to meet the antistatic properties of the material. As shown in Table 1, the surface resistivity of the PVC conductive composite material obtained using the preparation method provided in this invention and the preparation methods provided in prior art documents 1-4 both meet the requirements.
[0083] Examples 5-8
[0084] Examples 5-8 are based on Example 2, but the amount of silane coupling agent added is changed. The amount of silane coupling agent added in each example and the performance of the products prepared are shown in Table 2.
[0085] Table 2. Raw material component content and product test results for Examples 5-8
[0086]
[0087] Note: The silane coupling agent is γ-aminopropyltriethoxysilane, the toughening agent DOTP is dioctyl terephthalate, and the dispersant PETS is pentaerythritol stearate.
[0088] The test methods are as follows:
[0089] Conductivity test: Conductivity was tested using a weighted resistance meter (PRS-801), and the sample size was a 100×100×3mm square plate.
[0090] Mechanical property testing: Notched impact strength of simply supported beams, using a pendulum impact testing machine.
[0091] Surface smoothness: The surface condition of the extruded sample is observed by the naked eye and divided into three levels: excellent, good, and poor. Excellent means that there are almost no pits on the surface, good means that there are a few pits on the surface, and poor means that there are a lot of pits on the surface.
[0092] As can be seen from Table 2, the surface resistivity, notched impact strength, and appearance of Examples 5-8 are all better than those of Comparative Examples 1-4, that is, the products of the present invention have better conductivity, impact resistance and better appearance.
[0093] The surface resistivity can achieve the expected conductivity, but when the content of silane coupling agent reaches a certain amount, the impact resistance no longer has a significant improvement effect. Therefore, the preferred weight ratio of carbon nanotubes to silane coupling agent is 1:0.3 to 0.5.
[0094] Examples 9-12
[0095] Examples 9-12 are based on Example 2, except that the amount of dispersant added is changed. The amount of dispersant added in each example and the performance of the products prepared are shown in Table 3.
[0096] Table 3. Raw material component content and product test results for Examples 9-12
[0097]
[0098] Note: The silane coupling agent is γ-aminopropyltriethoxysilane, the toughening agent DOTP is dioctyl terephthalate, and the dispersant PETS is pentaerythritol stearate.
[0099] The test methods are as follows:
[0100] Conductivity test: Conductivity was tested using a weighted resistance meter (PRS-801), and the sample size was a 100×100×3mm square plate.
[0101] Mechanical property testing: Notched impact strength of simply supported beams, using a pendulum impact testing machine.
[0102] Surface smoothness: The surface condition of the extruded sample is observed by the naked eye and divided into three levels: excellent, good, and poor. Excellent means that there are almost no pits on the surface, good means that there are a few pits on the surface, and poor means that there are a lot of pits on the surface.
[0103] As can be seen from Table 3, the notched impact strength in Example 9 is relatively low, which may be due to the small amount of dispersant used, resulting in ineffective dispersion of carbon nanotubes. In contrast, the surface resistivity, notched impact strength, and appearance of Examples 10-12 are all better than those of Comparative Examples 1-4, indicating that the products of this invention have better conductivity, impact resistance, and appearance.
[0104] Provided that the surface resistivity can basically achieve the expected conductivity, when the content of dispersant reaches a certain amount, it no longer has a significant effect on improving the impact resistance and conductivity. Therefore, the preferred weight ratio of carbon nanotubes to dispersant is 1:0.6 to 0.8.
[0105] Examples 13-16
[0106] Preparation of carbon nanotube and carbon black composite conductive filler
[0107] Step SA, take M1 part of carbon nanotubes and put them into M A A portion of a mixture of 68% concentrated HNO3, 30% hydrochloric acid, and deionized water in a volume ratio of a:b:c, was dissolved in water at temperature T. A1 Stirring and acidification treatment at ℃ t A1 For hours, the carbon nanotubes were acidified and oxidized for grafting, then washed and filtered 6-8 times with water until the filtrate was neutral. At T... A2 The filter cake was dried at ℃ to constant weight to obtain the treated carbon nanotubes.
[0108] Step SB: Place M2 parts of carbon black in a sealed environment and add M... B maleic anhydride in portions, and heated to T. B1 The temperature of ℃ vaporizes maleic anhydride, and the sealed container is then sealed. B1 Hours, then wash with water n B Next, and in T B2 Drying at ℃ temperature t B2 Hours. The carbon black here is carbon black N220.
[0109] Step SC: Add the treated carbon nanotubes, treated carbon black, M3 parts dispersant, and M4 parts silane coupling agent to the grinding mill in the specified proportions, and then... C rpm rotation speed, diameter d mm zirconium ball, grinding t C Within hours, carbon nanotubes and carbon black composite conductive fillers are obtained.
[0110] Preparation of PVC conductive composite materials
[0111] Step S1: Add 100 parts of PVC resin powder, M6 parts of toughening agent, M7 parts of stabilizer, and M8 parts of antioxidant to a rotary mixer, and mix them evenly in powder form at T1℃ and R1 rpm to obtain PVC initial mixture.
[0112] Step S2: Divide the PVC premix into four equal portions. After adding carbon nanotube and carbon black composite conductive filler to the first portion, add more carbon nanotube and carbon black composite conductive filler every 10-30 minutes. Mix the carbon nanotube and carbon black composite conductive filler with the PVC premix in powder form at T2℃ and a stirring speed of R2 rpm to disperse them in a solid state, forming a premix. This method allows for predisposition and, more importantly, avoids the structural damage caused by stirring instead of extrusion shearing, thus minimizing disruption to the structure of the carbon nanotube and carbon black composite conductive filler.
[0113] The other steps are the same as those in Example 2.
[0114] Table 4. Raw material component content and product test results for Examples 13-16
[0115]
[0116]
[0117] Note: The silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane; the dispersant is ethylene bis-stearamide; TUBALL is single-walled carbon nanotubes from OCSiAl; GTW-290 is few-walled carbon nanotubes from Shandong Dazhan Nanomaterials Co., Ltd.
[0118] The test methods are as follows:
[0119] Conductivity test: Conductivity was tested using a weighted resistance meter (PRS-801), and the sample size was a 100×100×3mm square plate.
[0120] Mechanical property testing: Notched impact strength of simply supported beams, using a pendulum impact testing machine.
[0121] Surface smoothness: The surface condition of the extruded sample is observed by the naked eye and divided into three levels: excellent, good, and poor. Excellent means that there are almost no pits on the surface, good means that there are a few pits on the surface, and poor means that there are a lot of pits on the surface.
[0122] As can be seen from Table 4, Examples 13-16 differ from Example 2 only in the types of toughening agent, stabilizer, silane coupling agent, antioxidant, dispersant, and carbon nanotubes, as well as the mixed acid M. A The number of parts, maleic anhydride M BThe acid content is selected from any value between 0.4 and 0.6 times that of carbon black, and the acid-mixing ratio a:b:c is selected from any ratio between 1 and 3:1:2 and 3. T A1 Selected from any value between 70 and 90, t A1 and t B1 T is selected from any value between 1.5 and 3. B1 R is any value selected from 220 to 260. C The value is selected from any value between 500 and 1000, d is selected from any value between 2 and 20, and t is selected from any value between 500 and 1000. C The values are selected from 3 to 5, T1 and T2 are selected from 80 to 110, R1 is selected from 200 to 400, and R2 is selected from 150 to 250. The test results of the final products obtained in Examples 13 to 16 are almost identical to those of the product in Example 2, indicating that only the types of toughening agent, stabilizer, silane coupling agent, antioxidant, dispersant, and carbon nanotubes, as well as M, were changed. A M B a:b:c, T A1 t A1 t B1 T B1 R C , d, t C The values of T1, T2, R1, and R2 do not change the final physical properties of the product.
[0123] This invention provides a process for preparing PVC conductive composite materials using carbon nanotubes and carbon black composite conductive fillers. The combined usage of carbon nanotubes and carbon black is significantly reduced. Compared with PVC conductive composite materials prepared using pure carbon nanotubes, pure carbon black, or in-situ prepared carbon nanotube-carbon black composite fillers, the PVC conductive composite materials of this invention have improved mechanical properties and lower costs.
[0124] The present invention has been described in detail above with reference to the accompanying drawings and embodiments. Those skilled in the art can make various modifications to the present invention based on the above description. Therefore, certain details in the embodiments should not be construed as limiting the present invention, and the scope of protection of the present invention shall be defined by the appended claims.
Claims
1. A carbon nanotube and carbon black composite conductive filler, characterized in that... The composite conductive filler includes a composite of carbon nanotubes and carbon black obtained by ball milling and mixing surface-grafted carbon nanotubes and surface-grafted carbon black.
2. The carbon nanotube and carbon black composite conductive filler as described in claim 1, characterized in that... The weight ratio of carbon nanotubes to carbon black is 1:1 to 4, preferably 1:2 to 3.
3. The carbon nanotube and carbon black composite conductive filler as described in claim 2, characterized in that... The composite conductive filler further includes a silane coupling agent. Preferably, the weight ratio of the carbon nanotube to the silane coupling agent is 1:0.2 to 0.6, more preferably 1:0.3 to 0.
5. The silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
4. The carbon nanotube and carbon black composite conductive filler as described in claim 2, characterized in that... The composite conductive filler further includes a dispersant. Preferably, the weight ratio of the carbon nanotube to the dispersant is 1:0.4 to 1, more preferably 1:0.6 to 0.
8. The dispersant is one or two of ethylene bis-stearamide and pentaerythritol stearate.
5. A method for preparing the carbon nanotube and carbon black composite conductive filler according to claim 1 or 2, characterized in that, The method involves ball milling and grinding surface-grafted carbon nanotubes and surface-grafted carbon black to obtain a composite conductive filler of carbon nanotubes and carbon black.
6. The method as described in claim 5, characterized in that, The addition of a silane coupling agent before ball milling is preferably carried out in a weight ratio of carbon nanotubes to silane coupling agent of 1:0.2-0.6, more preferably 1:0.3-0.5, wherein the silane coupling agent is selected from at least one of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane; more preferably, the addition of a dispersant before ball milling is preferably carried out in a weight ratio of carbon nanotubes to dispersant of 1:0.4-1, more preferably 1:0.6-0.8, wherein the dispersant is one or both of ethylene bis-stearamide and pentaerythritol stearate.
7. The method as described in claim 5, characterized in that, The surface-grafted carbon nanotubes are carbon nanotubes with -COOH and / or -OH grafted onto their surfaces; preferably, the surface-grafted carbon nanotubes are carbon nanotubes grafted by acidification oxidation, preferably using concentrated nitric acid and hydrochloric acid for acidification oxidation grafting, more preferably, the mixed acid solution used for acidification oxidation grafting includes: 68% concentrated HNO3: 30% hydrochloric acid: deionized water in a volume ratio of 1-3:1:2-3, the acidification oxidation grafting temperature is 70℃-90℃, preferably 80℃, the acidification oxidation grafting time is 1.5 hours-3 hours, preferably 2 hours, more preferably, the acidified oxidation grafted carbon nanotubes are washed with water and dried; The carbon nanotubes are single-walled carbon nanotubes, few-walled carbon nanotubes, and / or multi-walled carbon nanotubes. The surface-grafted carbon black is carbon black with -COOH and / or -OH grafted onto its surface. Preferably, the surface-grafted carbon black is surface-grafted using vaporized maleic anhydride in a closed contact with carbon black. The grafting temperature is 220℃~260℃, preferably 240℃, and the grafting time is 1.5 hours~3 hours, preferably 2 hours. More preferably, the weight ratio of carbon black to maleic anhydride is 1:0.4~0.6, preferably 1:0.
5. More preferably, the surface-grafted carbon black is washed and dried.
8. The method as described in claim 5, characterized in that, The grinding is performed with grinding balls for 3 to 5 hours at a speed of 500 to 1000 rpm, preferably 700 to 800 rpm. Preferably, the diameter of the grinding balls is 2 to 20 mm, preferably 5 to 10 mm. Preferably, the grinding balls are zirconium balls.
9. The application of the carbon nanotube and carbon black composite conductive filler according to any one of claims 1 to 4 in the electrical conductivity, thermal conductivity and reinforcement of plastic and rubber products.
10. A PVC conductive composite material, characterized in that... The PVC conductive composite material includes carbon nanotube and carbon black composite conductive filler, PVC resin powder, toughening agent, stabilizer and antioxidant; preferably, based on 100 parts of PVC resin powder, the carbon nanotube is 3 parts, the carbon black is 3-12 parts, preferably 6-9 parts, the silane coupling agent is 0.6-1.8 parts, preferably 0.9-1.5 parts, the dispersant is 1.2-3 parts, preferably 1.8-2.4 parts, the stabilizer is 2-10 parts, the toughening agent is 5-20 parts, and the antioxidant is 0.1-1 parts.
11. The PVC conductive composite material as described in claim 10, characterized in that, The toughening agent is selected from one or more of the following: dioctyl phthalate, dibutyl phthalate, dioctyl terephthalate, epoxidized soybean oil, MBS, CPE and ACR; The stabilizer is selected from one or more of the following: lead salt composite stabilizers, organic-based stabilizers, organotin stabilizers, calcium-zinc composite stabilizers, barium-zinc composite stabilizers, and potassium-zinc composite stabilizers; The antioxidant is selected from one or more of antioxidant 168, antioxidant 1010 and antioxidant 1076.
12. A method for preparing the PVC conductive composite material of claim 10, characterized in that, The method includes the following steps: Step S1: PVC resin and additives are mixed to obtain PVC primary mixture; preferably, the additives are toughening agents, stabilizers and antioxidants; Step S2: The carbon nanotube and carbon black composite conductive filler are stirred and mixed with the PVC primary mixture to obtain a premix. Step S3: Pour the premix into an extruder and knead and extrude to obtain PVC conductive composite material.
13. The method for preparing PVC conductive composite material as described in claim 12, characterized in that, Step S3 involves adding the premix from the main feed port of a twin-screw extruder, and then extruding it through the twin-screw extruder to obtain a PVC conductive composite material. The temperatures in each zone of the twin-screw extruder are 80–100℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, 150–170℃, and 150–170℃, respectively, and the twin-screw speed is 200–300 rpm.
Citation Information
Patent Citations
An in-situ preparation method of a super-strong composite filler of carbon nanotubes and carbon black
CN108047495B